Characterization of PM10 and Impact on Human Health During the Annual Festival of Lights (Diwali) - Rajyalakshmi Garaga; Sri Harsha Kota (Journal of Health and Pollution, 2018)
Background. Diwali is a Hindu holiday observed each autumn in India, where it is known as the ‘celebration of lights’. Burning of fireworks on this day leads to air and noise pollution, causing adverse effects to human health. Objectives. To monitor and analyze air quality and noise levels in a residential college campus in northeast India over Diwali 2015. Methods. Components of PM10, including metals (cadmium (Cd), cobalt (Co), iron (Fe), zinc (Zn) and nickel (Ni)), ions (calcium (Ca2+), ammonium (NH4+), sodium (Na+), potassium (K+), chloride (Cl−), nitrate (NO3−) and sulfate (SO4 2−)) and bacterial counts were studied for a period of ten days in November 2015. In addition, a health-based survey of patients attending the institute's hospital during those days was conducted to evaluate the risk level due to fireworks burning. Results. The mean PM10 concentration during Diwali, 311 μg/m3, was 81% higher than other days and 3.1-times higher the Indian National Ambient Air Quality Standards. While noise levels were increased by 65%, the concentration of bacteria in PM10 was reduced by 39% during Diwali compared to other days. The concentrations of metals, cations and anions were increased by 51%, 72% and 77%, respectively. A health study conducted during the analysis period revealed an increase in hospital admissions in the campus due to respiratory symptoms. The higher concentrations of metals during the Diwali period resulted in a 0.5% increase in the hazard index. Conclusions. The present study suggests that reducing fireworks during Diwali could reduce pollutant concentrations and result in potential health benefits. Participant Consent. Obtained Ethics Approval. The study and survey design were approved by the Institutional Bioethics Committee of the Indian Institute of Technology, Guwahati. Competing Interests. The authors declare no competing financial interests